2022
DOI: 10.5194/essd-14-3961-2022
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia pollen dataset for exploring the potential ecological indicators in deep time

Abstract: Abstract. Artemisia, along with Chenopodiaceae, is the dominant component growing in the desert and dry grassland of the Northern Hemisphere. Artemisia pollen with its high productivity, wide distribution, and easy identification is usually regarded as an eco-indicator for assessing aridity and distinguishing grassland from desert vegetation in terms of the pollen relative abundance ratio of Chenopodiaceae/Artemisia (C/A). Nevertheless, divergent opinions on the degree of aridity evaluated by Artemisia pollen … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…SEM images can be used to improve the performance of pollen identification in practice [ 20 , 21 , 22 , 23 , 24 , 25 ], since the high resolution of SEM unlocks the potential to provide the obvious differentiation of the pollen grains for the experts (as shown in Table 1 ). In our study, we obtained 1324 SEM pollen images in total (805 Cupressaceae, 248 Fraxinus and 271 Ginkgo) from Beijing Meteorological Center, which served as the data for our automatic pollen identification task.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SEM images can be used to improve the performance of pollen identification in practice [ 20 , 21 , 22 , 23 , 24 , 25 ], since the high resolution of SEM unlocks the potential to provide the obvious differentiation of the pollen grains for the experts (as shown in Table 1 ). In our study, we obtained 1324 SEM pollen images in total (805 Cupressaceae, 248 Fraxinus and 271 Ginkgo) from Beijing Meteorological Center, which served as the data for our automatic pollen identification task.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Therefore, SEM images have exhibited significant potential to enhance the ability to accurately identify airborne pollens in an automatic manner for the palynology community [ 19 ]. Currently, some preliminary research works on SEM-based automatic pollen identification have been reported [ 20 , 21 , 22 , 23 , 24 , 25 ]. An early example of an SEM-image-based method was [ 20 ], in which the authors extracted the texture features to train a Fisher linear discriminant classifier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of a species to adapt and survive in both warm and cool environments provides a highly valuable defence mechanism against extinction. The distribution and vegetative and reproductive development of these plants are influenced by geographical location, local climate, and prevailing meteorological conditions (Anibogwu et al, 2021;Lu et al, 2022).…”
Section: Importance Of Artemisia Spp Medicinal Plantsmentioning
confidence: 99%